Literasi Perpajakan Dengan Sistem E-Filling Dan E-Billing Di KPP Tegalsari Surabaya - Siti Nur Zazilah; Ayu Sri Rahmawati; Rismawati Sitepu (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The background of this research is to understand the tax literacy system towards taxpayer compliance in the tax collection system with the self-assessment method, implementing e-filing and e-billing with the aim of making it easier for the public to submit Annual SPT electronically. The method Descriptive qualitative approach method, which means that researchers identify information system problems regarding taxpayer compliance at KPP Pratama Tegalsari Surabaya, is used in this study.